2022
DOI: 10.3390/socsci11080371
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Themes on Factors Influencing Career and Employment Decisions: Voices of Individuals with Disabilities from Four Gulf Countries

Abstract: Understanding the range of factors influencing career and employment decisions of individuals with disabilities is crucial for policy makers, businesses, and other stakeholders to support and integrate individuals with disabilities in the economic and social capital of the Arab-Gulf. The purpose of this sttudy was to investigate the factors that influence individuals with disabilities in making decisions about their career and employment. We explore how Arab adults with disabilities explain their career and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Adequate social support must be accessible to university students with disabilities because it may significantly contribute to academics [32]. It has been observed that individuals, despite their disabilities, with university degrees have better prospects of employment and are able to live healthier and more productive lives than those without higher education [33].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate social support must be accessible to university students with disabilities because it may significantly contribute to academics [32]. It has been observed that individuals, despite their disabilities, with university degrees have better prospects of employment and are able to live healthier and more productive lives than those without higher education [33].…”
Section: Discussionmentioning
confidence: 99%
“…The low rates in Arab countries may be attributed to methodological issues in the data collection and the social stigma associated with disability (UN Economic and Social Commission for Western Asia, 2018). Negative attitudes towards persons with disabilities are prevalent in the Arab region (Al-Hendawi et al, 2022). Persons with disabilities often face disadvantages in terms of education, health, employment, and their participation in political and public life (United Nations Economic and Social Commission for Western Asia et al, 2023).…”
Section: Introductionmentioning
confidence: 99%